THE EFFECT OF ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) DISCLOSURE ON COMPANY’S PROFITABILITY & VALUE IN THE SRI-KEHATI INDEX 2015 - 2020 - Johan; Gladys Kerenhapukh Toti (Universitas Trisakti, 2022)
Purpose - The aim of this research is to examine the impact of environmental, social, and governance (ESG) disclosure on company profitability and value in the SRI-KEHATI index from 2015 to 2020.Design/methodology/approach - The methodology used is a quantitative technique based on secondary data. Statistical software was used to do the data analysis. The study data is derived from the Thomson Reuters ESG Database and the financial reports of seven Indonesia Stock Exchange nonfinancial firms chosen with the purposive sampling method. The research includes three independent factors (environmental score, social score, and governance score), as well as control variables (leverage) and dependent variables (profitability with return on equity as a proxy and company value with Tobin’s Q as a proxy).Findings - This research concludes that companies with good corporate governance had a beneficial effect on both dependent variables in this research. Meanwhile, the environmental score has a negative impact on return on equity and company value. In addition, the social score has a negative impact on company value and gives no effect on return on equity. Stakeholders may utilize the implications of this finding to assess the company's performance.Originality/Value - The outcome of this research can be used to present a successful model for non-financial companies in Indonesia listed in the SRI-KEHATI Index to implement the role of ESG disclosure in performance. Keywords: ESG, firm value, profitability, strategic management